Assessing cloudiness effect on soybean yield in the Southeast Brazil (Agrometeoros, 2020)
The solar radiation is one of the most important weather variables for determining the potential yield of agricultural crops. Soybean is the main Brazilian agricultural commodity, with great social and economical importance for the country. It is well recognized that cloudiness is a limiting factor for crop growth rate. Few studies have been conducted to systematically evaluate how much cloud affect soybean yield and none, to our knowledge, is available for tropical soybean. The objective of this paper was to quantify the implications of cloudiness on soybean growth and development in tropical Brazil. To do so, experimental data associated with the simulations of the DSSAT/CROPGRO (DC) model was used, and two treatments were simulated: a) the first used measured solar radiation and b) the second used estimated solar radiation for non-cloud days. Thus, based on the model output variables (growth rate of aerial dry matter, grain yield, specific leaf weight, and light saturation point) and comparing the data with the literature review. We found that simulations exhibited an increase in the dry matter production rate of up to 23%, during days of clear sky, resulting in a yield increase between 26 and 37%. Also, the DC could simulate some adaptation in the plant when the solar radiation changes, like the specific foliar weight and the light-saturated photosynthesis rate.